Ali starost vpliva na izbor najbolj priljubljenih športnorekreativnih dejavnosti? - Dolenc, Maja (Šport (Ljubljana), 2010)
The aim of the study was to investigate the most popular sport activities among Slovenian population according to age. The sample consisted of 1286 persons aged 15 years and above (average age 46,6 18,9 years), there were 190 persons in the first age group (15-24 let), 208 in second (25-34), 227 in third (35-44), 209 in fourth (45-54), 177 in fifth (55-64) and 275 aged 65 years and above. They filled in a questionnaire about their sport activities. The results show that people in all age groups prefer to walk and swim. Football was placed third in the youngest age group (35 %), while in all others there was cycling.
Keywords: odrasli; raziskave; rekreacija; Slovenija; starost; šport; športna aktivnost